Facilitating Early Breast Milk Expression in Mothers of Very Low Birth Weight Infants. Issue 2 (March 2018) - Parker, Leslie Ann; Hoffman, Jacqueline; Darcy-Mahoney, Ashley
Abstract: Background: Although early initiation of human milk (HM) expression after birth is known to increase lactation success in mothers of very low birthweight (VLBW) infants, initiation is frequently delayed, potentially decreasing both short- and long-term HM production. Obstetrical (OB) nurses are typically the healthcare provider responsible for facilitating the initial HM expression session. As delays in initiation are common, it is likely that nurses experience obstacles to facilitation of an early initiation of HM expression. The purpose of this study was to determine barriers OB nurses perceive in facilitating early initiation of HM expression in mothers of VLBW infants. Study Design and Methods: An online survey was administered to nurses from three tertiary care OB units in Florida to determine perceived barriers to early initiation of HM expression in mothers of VLBW infants. Results: Eighty-three nurses completed the survey. The following barriers were identified: (1) lack of time and personnel to assist mothers with HM expression, (2) nurse's perception of the mother's acuity level, and (3) nurse's perception of maternal pain and stress. Discrepancies between nursing judgment, action, and knowledge of unit policies were evident. Clinical Implications: Obstetric nurses encounter barriers when facilitating early HM expression in mothers giving birth to VLBW infants. It is possible these barriers could be removed through improvements in education, use of innovative staffing strategies, and maintenance of evidence-based policies. Abstract : Early initiation of breastfeeding or breast milk expression is important soon after birth to enhance milk production. Often mothers who give birth preterm have a cesarean, which can delay milk expression. This survey of maternity nurses offers information about their perceived barriers to timely breastmilk expression for mothers of very low birth weight babies.